Gestão de recursos informacionais: elaboração de plano de desbaste para a biblioteca do Instituto Federal de Sergipe (IFS) - campus São Cristóvão - Oliveira, Jacilene de Jesus (2020)
The study addressed the need for thinning activity in the library of the São Cristóvão Campus of the Federal Institute of Education, Science and Technology of Sergipe, with the objective of developing a thinning plan that guides the withdrawal of information resources from the collections, based on pre-established criteria marked out by scientific literature and by the Factor of Use method. The study also characterized the thinning in the activity of developing collections, identifying methods and criteria adopted in carrying out this activity and described the main advantages of using the thinning plan in collections of informational materials. The methodological proposal was applied in nature, exploratory and descriptive and with a quantitative approach, with the Usage Factor method used to classify and identify relevant data about the volume of use of library collections that were categorized into five areas of knowledge (Informatics, Mathematics, Philosophy, Portuguese Language and Politics). The results showed mismatches in all areas studied, since Informatics and Mathematics are overused, indicating the urgency of duplicating some of their titles, and the areas of Philosophy, Portuguese Language and Politics are underused indicating the need for realization. thinning of some of its titles. Thus, the study highlights the need to implement a thinning plan in the library of Campus São Cristóvão as a measure of ensuring that the use of collections, that is, that the purpose of the library actually meets the information needs of its users, in For this reason, the thinning plan was prepared.